Land Management of the Areas of High Landscape Values: An Economic Model - Wańkowicz, Wiesław (Comparative Economic Research. Central and Eastern Europe, 2013)
This paper presents selected results of the research entitled Planning the Space of High Landscape Values, Using Digital Land Analysis, with Economic Appraisal, supervised by Dr. Paweł Ozimek, Cracow Technical University, conducted since 2009. Usually, we do not pay attention to surrounding landscapes in our everyday life. However, for the persons who deal with spatial planning, geography, natural environment, or cultural heritage, the validity and value of landscape are the terms which do not have to be defined. The first part of the paper is dedicated to the landscape features that decide about its value. The author discusses whether those features are the same as those we want to protect and how we can appraise landscape values. The next part contains an analysis of the economic bases of development. In reference to space, the analysis and opinion on land use in the context of the development of usable functions are essential. Consequently, the identification of the limitations connected with the protection of landscape and delimitation of the areas on which such limitations exist are required. Another component consists in the determination of the land requirements associated with existential and economic needs of the local population. Such a general balance of needs and requirements is the starting point of the adoption of development policies and action programmes. The programmes should include the location of individual projects and capital investments on land, as well as their proper timing co-ordination. Owing to the complexity of the tasks, the option analysis is the preferred method of search for the best possible solution. The reconciliation of individual land use (title to land), public and business land uses, with the protection of environmental and cultural values, can be difficult or next to impossible to attain. Therefore, we need some mechanisms to compensate the losses occurring in individual interests and in local, regional, or national development. The choice of options for local or regional development is based on balancing the costs and benefits that depend on the sizes of both protected and non-protected areas. In conclusion, the author attempts at answering the questions whether the landscape and landscape values can be saved owing to their economic assets, and what instruments should be implemented to utilize economic mechanisms of protection.